AESTHETIC EDUCATION OF MIDDLE CLASS STUDENTS BY MEANS OF EXPRESSIVE READING - Kolomiets, N.Ye.; Yaremenko, N.V. (Educational Dimension, 2004)
Different problems and aspects of bringing up of spirit among young generation in studiing Ukrainian literature are opened in this article.